2019
DOI: 10.1002/jcp.28844
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum polysaccharide reduces melanogenesis by inhibiting the paracrine effects of keratinocytes and fibroblasts via IL‐6/STAT3/FGF2 pathway

Abstract: Our previous study found that Ganoderma lucidum polysaccharide (GLP), bioactive ingredients from Ganoderma lucidum, protected fibroblasts from photoaging. However, whether GLP can affect melanogenesis in melanocytes through regulating paracrine mediators that secreted by keratinocytes and fibroblasts is unclear. We aimed to investigate the efficacy and mechanisms of action of GLP in melanogenesis by regulating paracrine effects of keratinocytes and fibroblasts. The effect of GLP on cell viability affected by G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 48 publications
0
16
0
3
Order By: Relevance
“…Some studies to date reported the application of herbal polysaccharide in melanogenesis to inhibit melanin production . However, in this study, CDP promoted melanogenesis in melanocytes, and this effect was further confirmed after comparison with α‐MSH.…”
Section: Discussionmentioning
confidence: 46%
“…Some studies to date reported the application of herbal polysaccharide in melanogenesis to inhibit melanin production . However, in this study, CDP promoted melanogenesis in melanocytes, and this effect was further confirmed after comparison with α‐MSH.…”
Section: Discussionmentioning
confidence: 46%
“…Ubtan (UF-1 to UF-4) rhizome of Curcuma longa L. seeds of Cicer arietinum L. heartwood of Santalum album L. With the ratio of 2:2:2 (UF-1), 1:2:2 (UF-2), 2:1:2 (UF-3) and 2:2:1 (UF-4) antioxidant; sun protection; suppressing tyrosinase activity in vitro: mushroom tyrosinase (Hu et al, 2019;Jiang et al, 2019). Goji berry (Lycium chinense Mill.)…”
Section: Herbal Extractsmentioning
confidence: 99%
“…leaves extract is found to be effective in moisturizing, anti-aging, freckle-removing, and skin whitening ( Jimenez-Perez et al., 2018 ). Ganoderma lucidum polysaccharides can reduce melanogenesis by inhibiting cAMP/PKA and ROS/MAPK signaling pathways, as well as inhibiting paracrine effects ( Hu et al., 2019 ; Jiang et al., 2019 ). Goji berry ( Lycium chinense Mill.)…”
Section: The Effects and Problems Of Traditional Asian Herbs In Skin mentioning
confidence: 99%
“…GLP can antagonize UVB-induced skin pigmentation in vivo (Hu et al 2019a(Hu et al , 2019b. GLP can inhibit the paracrine effects of keratinocytes and fibroblasts via the fibroblast growth factor (FGF2)/MAPK pathway to decrease melanogenesis in melanocytes (Jiang et al 2019). G. lucidum can treat pigmentary dermatosis such as solar lentigo, chloasma, freckles, and senile plaques.…”
Section: Anti-melanogenesis Effectsmentioning
confidence: 99%